2021
DOI: 10.7759/cureus.17615
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Parents of Thalassemic Child to Thalassemia in Pakistan

Abstract: BackgroundThalassemia is an inherited blood disorder characterized by reduced hemoglobin synthesis. Aim of our study is to assess the parental knowledge of thalassemia patients and their awareness regarding treatment and preventive measures against thalassemia. MethodsIt is an observational study done at Ali Zaib Foundation Thalassemia Center in Sahiwal, Pakistan, in May 2019. One hundred parents were enrolled in this study and a subjective questionnaire was used to collect data through direct structured surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…Following the weathering test on the UV absorber-coated samples, the tensile strength remained at 20 MPa, and the modulus was recorded at 1156 MPa. These results demonstrate the effectiveness of the UV absorber in enhancing the performance of the films under weathering conditions, with minimal impact on their strength and hydrophobicity, and are in line with environmental management practices [30].…”
Section: Tensile Strength and Modulussupporting
confidence: 76%
“…Following the weathering test on the UV absorber-coated samples, the tensile strength remained at 20 MPa, and the modulus was recorded at 1156 MPa. These results demonstrate the effectiveness of the UV absorber in enhancing the performance of the films under weathering conditions, with minimal impact on their strength and hydrophobicity, and are in line with environmental management practices [30].…”
Section: Tensile Strength and Modulussupporting
confidence: 76%
“…Hira Saleem et al [7] . recently demonstrated that a chemical compound, nitro benzaldehyde when injected directly into the tumour and subjected to beam of ultraviolet (UV) light, can eliminate cancer cells from the body within two hours.…”
Section: Introductionmentioning
confidence: 99%
“…It is characterised by reduced (ᵦ+) or no (βᴼ) synthesis of the beta-globin chain of haemoglobin because of mutation on the short arm of chromosomal 11. 6,7 More than 200 distinctive thalassemia-causing mutations have been distinguished in the beta globin gene. 8 Point mutations are most frequent.…”
Section: Introductionmentioning
confidence: 99%